Bank specialization and corporate innovation - Hans Degryse; Olivier De Jonghe; Leonardo Gambacorta; Cédric Huylebroek (National Bank of Belgium, 2024)
Theory offers conflicting predictions on whether and how lenders' sectoral specialization would affect firms' innovation activities. We show that the sign and magnitude of this effect vary with the degree of "asset overhang" across sectors, which is the risk that a new technology has negative spillovers on the value of a bank's legacy loan portfolio. Using both patent data and micro-level innovation survey data, we find that lenders' sectoral specialization improves innovation for firms operating in sectors with low asset overhang, but impedes innovation for firms operating in sectors with high asset overhang. These results hold for two distinct measures of asset overhang and using bank mergers as a source of exogenous variation in bank specialization. We further show that these heterogeneous effects arise through financial contracting. Overall, our findings provide novel insights into the dual facets of bank specialization and, more broadly, the link between banking and innovation.
Keywords: G20; O30; L20; 330; Bank specialization; Bank lending; Corporate innovation; Asset overhang; Financial frictions